2014
DOI: 10.1080/15685551.2014.971391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new optically active poly(acrylamide/methacrylurea-co-vinyl acetate) copolymers with dansyl units

Abstract: Novel optically active copolyacrylates synthesized by conventional radical polymerization of R/S-(+/−)-α-ethylbenzylacrylamide (R/S-EBzA) or R/S-(+/−)N-methacryloyloxyehtyl-N′-α-ethylbenzyl(urea) (R/S-MEBzU) and the vinyl acetate (VAc) in the presence of 1,1′-azobis (cyclohexanecarbonitrile) as the initiator showed optical rotation values ([α] D 23 ) of +45°/−50°for R/S-EBzA-co-VAc and of −40°in the case of S-MEBzU-co-VAc. Next, the hydrolysis reaction of the synthesized copolymers was accompanied of their che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In view of our previous studies related of the photophysical aspects of some macromolecular fluorophores in the field of chemical sensors which reflected some changes in their microenvironment such as polarity, fluidity, order, molecular mobility, pH, or electric potential, we have investigated further the absorption and emission behavior of a pyrene‐substituted chiroptical copolyacrylate by adding of various nitroaromatics (picric acid, nitrobenzene, o ‐nitrophenol, p ‐nitrotoluene) in polar medium, using UV/vis and fluorescence quenching studies. The absorption spectrum of poly(Ac‐ L ‐Ala‐ co ‐Ac‐ L ‐His)‐Py in DMF solution (Figure ) showed four absorption bands located at 278, 314, 328, and 345 assigned to the pyrene‐rings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of our previous studies related of the photophysical aspects of some macromolecular fluorophores in the field of chemical sensors which reflected some changes in their microenvironment such as polarity, fluidity, order, molecular mobility, pH, or electric potential, we have investigated further the absorption and emission behavior of a pyrene‐substituted chiroptical copolyacrylate by adding of various nitroaromatics (picric acid, nitrobenzene, o ‐nitrophenol, p ‐nitrotoluene) in polar medium, using UV/vis and fluorescence quenching studies. The absorption spectrum of poly(Ac‐ L ‐Ala‐ co ‐Ac‐ L ‐His)‐Py in DMF solution (Figure ) showed four absorption bands located at 278, 314, 328, and 345 assigned to the pyrene‐rings.…”
Section: Resultsmentioning
confidence: 99%
“…In previous articles, our group reported data concerning a series of new fluorescent and optically active poly(meth)acrylates with side chains containing amino acids moieties, such as phenylalanine, serine, leucine, etc., along with the study of different fluorescent units, namely fluorescein‐isothiocyanate, pyrene, stilbene, and so on . In this context, the objective of the present work is focused on the study of a side chain alanine and histidine containing copolyacrylate synthesized through conventional free radical polymerization, for which N ‐acryloyl‐ L‐ alanine and N ‐acryloyl‐ L‐ histidine have been chosen as monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethylamino moiety works as the electron donor while sulfonic acid group acts as the acceptor. Because of these characteristics, dansyl fluorophore was widely used as fluorescent probe for the detection of various materials [18][19][20][21][22] or as a label for bio-imaging [36,37]. …”
Section: Resultsmentioning
confidence: 99%
“…Murariu et al prepared optically active dansyllabeled copolyacrylates for sensitive and selective detection of transition metal ions. They showed that the dansyl side-functional copolymers selectively responded the presence of Fe 2+ cations [22]. Dansyl-containing polymers were mainly used for the fluorescent detection of ionic species.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al produced thermoresponsive microgels, based on dansyl-containing poly(N-isopropylacrylamide) (PNIPAM), for the selective fluorescent detection of Cu 2+ cations [29]. Murariu and Buruiana prepared dansyl-labelled poly(acrylamide/methacrylurea-co-vinyl acetate) copolymers for the fluorescent sensing studies towards some organic acids (1-S-camphorsulfonic acid and p-toluenesulfonic acid) and cations (H + , Cu 2+ , Hg 2+ , and Fe 2+ ) [30]. Recently, we have synthesized dansyl end-functional phosphazene-cored poly(ε-caprolactone) star polymer and employed as a selective fluorescent probe for the detection of Pb 2+ [1].…”
Section: Introductionmentioning
confidence: 99%